Gender, law and justice in a global market - Stewart, Ann (Cambridge University Press CambridgeGB, 2011)
Considers the way in which 'gender contracts' relating to work and care contribute to gender inequalities worldwide. Explores how economies in the Global North stimulate desires and create deficits in care and belonging, which are met through transnational movements, and traces the way in which transnational economic processes and discourses of rights and care create relationships between Global South and Global North. Focuses on African women who produce fruit and flowers for European consumption; body workers who migration to meet deficits in 'affect' through provision of care and sex; and British-Asian families who seek belonging through transnational marriages.